COGNITIVE SCIENCE OF RELIGION AND FOLK THEISTIC BELIEF: with Daniel Lim, "Cognitive Science of Religion and Folk Theistic Belief"; and Hans van Eyghen, "Two Types of 'Explaining Away' Arguments in the Cognitive Science of Religion.". Issue 4 (December 2016) - Lim, Daniel
Abstract: Cognitive scientists of religion promise to lay bare the cognitive mechanisms that generate religious beliefs in human beings. Defenders of the debunking argument believe that the cognitive mechanisms studied in this field pose a threat to folk theism. A number of influential responses to the debunking argument rely on making two sets of distinctions: (1) proximate/ultimate explanations and (2) specific/general religious beliefs. I argue, however, that such responses have drawbacks and do not make room for folk theism. I suggest that a detour through the literature in the philosophy of mind regarding the problem of mental causation regarding nonreductive physicalism can provide a way for preserving folk theism without doing violence to the way cognitive science of religion is being practiced today. More specifically, I believe there is a way of responding to the debunking argument that does not require a rejection of the causal premise.